México y Ecuador: un estudio comparativo de remesas e impacto macroeconómico - Jara-Alba, Carol; López-Guzmán, Tomás (Ciencia UNEMI, 2015)
Remittances from migrants have been a monetary source that has helped underprivileged households and consequently the economies of the countries from which these migrants come. This article provides a descriptive and historical study in order to carry out a comparative analysis of Mexican and Ecuadorian remittances during the period 1995 to 2009, years in which both countries faced severe economic crises. The study will identify similarities and differences in the evolution of remittances and their impact on the macroeconomic variables in international trade.